Iconicity as an organizing principle of the lexicon - Erin E. Campbell; Zed Sevcikova Sehyr; Elana Pontecorvo; Ariel Cohen-Goldberg; Karen Emmorey; Naomi Caselli (Proceedings of the National Academy of Sciences, 2025)
The view that words are arbitrary is a foundational assumption about language, used to set human languages apart from nonhuman communication. We present here a study of the alignment between the semantic and phonological structure (systematicity) of American Sign Language (ASL), and for comparison, two spoken languages—English and Spanish. Across all three languages, words that are semantically related are more likely to be phonologically related, highlighting systematic alignment between word form and word meaning. Critically, there is a significant effect of iconicity (a perceived physical resemblance between word form and word meaning) on this alignment: words are most likely to be phonologically related when they are semantically related and iconic. This phenomenon is particularly widespread in ASL: half of the signs in the ASL lexicon are iconically related to other signs, i.e., there is a nonarbitrary relationship between form and meaning that is shared across signs. Taken together, the results reveal that iconicity can act as a driving force behind the alignment between the semantic and phonological structure of spoken and signed languages, but languages may differ in the extent that iconicity structures the lexicon. Theories of language must account for iconicity as a possible organizing principle of the lexicon.